Biocompatibility and biodegradation of poly(lactic acid) (PLA) and an immiscible PLA/poly(ε-caprolactone) (PCL) blend compatibilized by poly(ε-caprolactone-b-tetrahydrofuran) implanted in horses - Carvalho, Júlia R. G. [UNESP]; Conde, Gabriel [UNESP]; Antonioli, Marina L. [UNESP]; Dias, Paula P.; Vasconcelos, Rosemeri O. [UNESP]; Taboga, Sebastião R. [UNESP]; Canola, Paulo A. [UNESP]; Chinelatto, Marcelo A.; Pereira, Gener T. [UNESP]; Ferraz, Guilherme C. [UNESP] (Springer Nature, 2020)
This paper focuses on the biocompatibility and biodegradation of PLA and a recently developed PLA/PCL blend containing an in vitro nontoxic compatibilizer based on a low-molecular-weight triblock copolymer derived from ε-caprolactone and tetrahydrofuran. The polymers were implanted subcutaneously in the lateral surface of the neck of horses. Physical examination, plasma fibrinogen (PF) analysis, infrared thermography (IT), mechanical nociceptive threshold (MNT) analysis, and ultrasonography were performed. After 24 weeks, the biomaterials were removed for histochemical analysis using hematoxylin-eosin (HE) and picrosirius-hematoxylin (PSH) staining. Scanning electron microscopy (SEM) was employed to determine changes in the surface morphology of the PLA and PLA/PCL blend. There were no clinical or PF changes. IT indicated a transient increase in cutaneous temperature (CT), while MNT decreased after the procedure in both the implanted groups. Ultrasonography revealed edema after the procedure and the loss of echogenicity of the polymers after implantation. Both polymers elicited a foreign body response under microscopic analysis. The PSH technique revealed a fibrotic reaction with collagen deposition around the polymers. SEM showed surface roughness, suggesting a biodegradation process. In conclusion, PLA and the PLA/PCL blend were biocompatible and biodegradable, with potential for use in equine medicine.